The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.oooo.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of computed tomographic scanner parameters and 3-dimensional volume rendering techniques on the accuracy of linear, angular, and volumetric measurements of the mandible

Abstract: Objectives This study investigates the effect of scanning parameters on the accuracy of measurements from three-dimensional multi-detector computed tomography (3D-CT) mandible renderings. A broader range of acceptable parameters can increase the availability of CT studies for retrospective analysis. Study Design Three human mandibles and a phantom object were scanned using 18 combinations of slice thickness, field of view, and reconstruction algorithm and three different threshold-based segmentations. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 40 publications
1
43
0
7
Order By: Relevance
“…The objective of this study was to quantify and compare dimension fidelity as some of the process variables are systematically changed. Other studies have investigated the impact of CT scanning parameters on accuracy of volume-rendered models [16], but this is one of the first studies to quantitatively investigate the geometric accuracy of a complex anatomic structure throughout the acquisition, processing, and printing stages.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to quantify and compare dimension fidelity as some of the process variables are systematically changed. Other studies have investigated the impact of CT scanning parameters on accuracy of volume-rendered models [16], but this is one of the first studies to quantitatively investigate the geometric accuracy of a complex anatomic structure throughout the acquisition, processing, and printing stages.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the virtual repairs with the actual postoperative result using radiographic landmarks [12]. Standardized mandibular measurements were recorded using Prism 6.0 (GraphPad; San Diego, California) after all 10 users completed their surgical simulations of the three fracture cases using both systems.…”
Section: Standard Landmarks and Measurementsmentioning
confidence: 99%
“…Computed tomography (CT) scans are effective for in vivo imaging of osseous structures. Anatomical measurements (such as length, width and volume of bones) taken from CT scans have been verified on larger bones such as femurs, humeri and mandibles (Stull et al, 2013; Whyms et al, 2013). These studies have shown that measurements gathered from CT scans are accurate, but that scanning and reconstruction parameters are complex and must be precise.…”
Section: Introductionmentioning
confidence: 99%